Finding the Projection of a Third-Kind Ill-Posed Boundary Value Problem in the Heat Scattering Equation - Jabborovich, Rustamov Maxammadali; o’g’li, Ubaydullayev Noyob Nodir (International Journal on Orange Technologies, 2023)
This article proposes a projection method for finding the projection of a third-kind ill-posed boundary value problem in the heat scattering equation. Previous approaches have limitations in terms of accuracy and efficiency, and the proposed method overcomes these limitations by using a projection operator to obtain a well-posed problem. Numerical simulations demonstrate the effectiveness of the method, which has potential applications in various fields, such as heat transfer and material science. Further research can explore the applicability of the method to more complex problems and the extension of the method to other types of ill-posed problems.